The Effectiveness of chewing water apple and star fruit in reducing plaque scores on Students Dental Health Department of the Jambi Ministry of Health Polytechnic - Rosmawati, Rosmawati; Rusmiati, Rusmiati; S, Mardelita; E, Zahara (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: Plaque is a layer attached to the surface of the teeth consisting of microorganisms that grow on the surface of the teeth if someone ignores dental and oral hygiene. Plaque is the main cause of caries and periodontal disease. Efforts made to prevent or reduce plaque formation with mechanical plaque control by brushing teeth, chemical methods using mouthwash and natural methods by chewing fibrous and juicy fruits. Objective: to determine the difference in the effectiveness of chewing water guava and star fruit in reducing plaque scores in students majoring in dental health in Jambi. Method: this study is a quasi-experimental study using a pre-test and post-test design. Sampling using purposive sampling, the sample in this study amounted to 30 students divided into 2 groups. Result: in the group chewing water apple fruit the average value of plaque score reduction was (29.9) and the results of the statistical test p-value 0.000 <0.05 in the group chewing star fruit the average plaque score reduction was (33.7) and the results of the statistical test p-value 0.000 <0.05 In the independent T-Test unpaired difference test obtained a p-Value of 0.017 <0.05 meaning there is a significant difference between chewing using water apple fruit and star fruit. Conclusion: water apple fruit and star fruit are effective in reducing plaque scores. But star fruit is more effective in reducing plaque scores in students of the Dental Health Department of the Jambi Ministry of Health Polytechnic.